2012
DOI: 10.1371/journal.pone.0041255
|View full text |Cite
|
Sign up to set email alerts
|

TRIM27 Negatively Regulates NOD2 by Ubiquitination and Proteasomal Degradation

Abstract: NOD2, the nucleotide-binding domain and leucine-rich repeat containing gene family (NLR) member 2 is involved in mediating antimicrobial responses. Dysfunctional NOD2 activity can lead to severe inflammatory disorders, but the regulation of NOD2 is still poorly understood. Recently, proteins of the tripartite motif (TRIM) protein family have emerged as regulators of innate immune responses by acting as E3 ubiquitin ligases. We identified TRIM27 as a new specific binding partner for NOD2. We show that NOD2 phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 88 publications
3
69
0
2
Order By: Relevance
“…In contrast, TRIM21 negatively regulates type I IFN production mainly through promoting K48-linked ubiquitination and degradation of DDX41 [35]. Recently, TRIM27 was described to act as an E3 ligase that negatively regulates NOD2 by mediating its ubiquitination and proteasomal degradation [36]. Here we show that TRIM27 is a key E3 ligase that mediates K48-linked ubiquitination at Lys251 and Lys372 of TBK1 and promotes TBK1 proteasomal degradation, thus functioning as a negative regulator of type I IFN production.…”
Section: Discussionmentioning
confidence: 57%
“…In contrast, TRIM21 negatively regulates type I IFN production mainly through promoting K48-linked ubiquitination and degradation of DDX41 [35]. Recently, TRIM27 was described to act as an E3 ligase that negatively regulates NOD2 by mediating its ubiquitination and proteasomal degradation [36]. Here we show that TRIM27 is a key E3 ligase that mediates K48-linked ubiquitination at Lys251 and Lys372 of TBK1 and promotes TBK1 proteasomal degradation, thus functioning as a negative regulator of type I IFN production.…”
Section: Discussionmentioning
confidence: 57%
“…TRIM27 functions as an E3 ubiquitin ligase (20) and is capable of conjugating various types of polyubiquitin chains to different substrates. Ubiquitination by TRIM27 modulates the activity of a given substrate rather than inducing its proteasomal degradation with the exception of NOD2 which it degrades (21). Ubiquitination by TRIM27 reduces the activity of PIK3C2B in T cells (22), inhibits PTEN to activate AKT1 (23), modifies WASH1 of the WASH regulatory complex to facilitate actin polymerization (24), and upregulates USP7-dependent deubiquitination of RIPK1 in tumor necrosis factor (TNF)-dependent apoptosis (25).…”
mentioning
confidence: 99%
“…Shiina et al (2007) found the TRIM27 gene in a region of the chicken MHC-B using an extended gene map. Zurek et al (2012) reported that TRIM27 could degrade NOD2 to negatively regulate NOD2-mediated signalling, suggesting that TRIM27 could be a new candidate target of drug intervention in NOD2-associated diseases. Zoumpoulidou et al (2012) reported that the expression of TRIM27 was a modifier of disease incidence and progression and was related to the development of common human cancers, suggesting that TRIM27 is a potential target for intervention in cancer.…”
Section: Discussionmentioning
confidence: 99%